Melestarikan dan Mengembangkan Warisan Budaya: Kebijakan Budaya Semarangan Dalam Perspektif Sejarah - Dhanang Respati Puguh (Department of History, Faculty of Humanities, Diponegoro University, 2017)
Semarang has developed as a diverse city. The communities who lived in Semarang history has produced a hybrid culture patterned Semarang which in the next time become as